Financial forensics body of knowledge - Dorrell, Darrell D.; Gadawski, Gregory A. (Hoboken, N.J. : John Wiley & Sons, 2012)
'The definitive, must-have guide for the forensic accounting professionalA comprehensive and practical overview of civil and criminal forensic accounting methodology, Forensic Accounting Body of Knowledge defines the profession of forensic accounting, capturing and codifying methods that define the body of knowledge. Filled with practical forensic accounting tips, tools and techniques, the book contains contributions from US and global professionals spanning all aspects of the financial community, including the law enforcement, investment, investigative, and regulatory arenas. Provides immediately useful tools Includes more than 200 tips and techniques Globally relevant content, with cutting-edge counterterrorism forensic accounting methodology Supported by a continually updated Internet-based software application Offers contributions from twenty financial experts in law enforcement, investigative, and regulatory fields Accompanied by a frequently updated Internet-based software application, Forensic Accounting Body of Knowledge will refine financial information users' approaches, techniques, and methods with useful tools and tips that reflect the continually growing body of forensic accounting knowledge'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Financial crimes; Forensic accounting; Fraud investigation